Peran Mediasi Kepuasan Konsumen Dalam Meningkatkan Pengaruh Brand Leadership Terhadap Niat Pembelian Kembali - Wiko Rizki Wijaya; Hery Syahrial; Adelina Lubis; Haryaji Catur Putera Hasman (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
This study aims to determine whether consumer satisfaction mediates brand leadership on repurchase intentions. This research was conducted using a questionnaire distributed to 108 samples who are Shopee application users in Tanjung Rejo Village. The sampling technique used was non-probability sampling, namely convenience sampling. This type of research uses a quantitative approach. The data analysis technique used in this research is path analysis. The results of this study indicate that: 1) Quality variable (X1) has a positive and significant effect on Consumer Satisfaction. 2) Value variable (X2) has a positive but not significant effect on Consumer Satisfaction (Y1). 3) Innovation Variable (X3) has a positive and significant effect on Consumer Satisfaction. 4) Popularity variable (X4) has a positive and significant effect on Consumer Satisfaction (Y1). 5) Consumer Satisfaction Variable (Y1) has a positive and significant effect on repurchase intention (Y2). 6) Consumer Satisfaction mediates brand leadership on repurchase intention).